Mycobacterium indicus pranii Induced Memory T-Cells in Lung Airways Are Sentinels for Improved Protection Against M.tb Infection - Gupta, Ananya; Saqib, Mohd; Singh, Bindu; Pal, Lalit; Nishikanta, Akoijam; Bhaskar, Sangeeta (Frontiers in Immunology, 2019)
The lungs are the most vulnerable site for air-borne infections. Immunologic compartmentalization of the lungs into airway lumen and interstitium has paved the way to determine the immune status of the site of pathogen entry, which is crucial for the outcome of any air-borne infections. Vaccination via the nasal route with Mycobacterium indicus pranii (MIP), a prospective candidate vaccine against tuberculosis (TB), has been reported to confer superior protection as compared to the subcutaneous (s.c.) route in small-animal models of TB. However, the immune mechanism remains only partly understood. Here, we showed that intranasal (i.n.) immunization of mice with MIP resulted in a significant recruitment of CD4+ and CD8+ T-cells expressing activation markers in the lung airway lumen. A strong memory T-cell response was observed in the lung airway lumen after i.n. MIP vaccination, compared with s.c. vaccination. The recruitment of these T-cells was regulated primarily by CXCR3–CXCL11 axis in “MIP i.n.” group. MIP-primed T-cells in the lung airway lumen effectively transferred protective immunity into naïve mice against Mycobacterium tuberculosis (M.tb) infection and helped reducing the pulmonary bacterial burden. These signatures of protective immune response were virtually absent or very low in unimmunized and subcutaneously immunized mice, respectively, before and after M.tb challenge. Our study provides mechanistic insights for MIP-elicited protective response against M.tb infection.